A rise in the frequency of lasR mutant Pseudomonas aeruginosa among keratitis isolates between 1993 and 2021 - Shanks, Robert M. Q.; Atta, Sarah; Stella, Nicholas A.; Sundar-Raj, Chollapadi V.; Romanowski, John E.; Grewal, Arman S.; Shanks, Hazel Q.; Mumper, Sonya M.; Dhaliwal, Deepinder K.; Mammen, Alex; Callaghan, Jake D.; Calvario, Rachel C.; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Pseudomonas aeruginosa causes severe vision threatening keratitis. LasR is a transcription factor that regulates virulence associated genes in response to the quorum sensing molecule N-3-oxododecanoyl-L-homoserine lactone. P. aeruginosa isolates with lasR mutations are characterized by an iridescent high sheen phenotype caused by a build-up of 2-heptyl-4-quinolone. A previous study indicated a high proportion (22 out of 101) of P. aeruginosa keratitis isolates from India between 2010 and 2016 were sheen positive and had mutations in the lasR gene, and the sheen phenotype correlated with worse clinical outcomes for patients. In this study, a longitudinal collection of P. aeruginosa keratitis isolates from Eastern North America were screened for lasR mutations by the sheen phenotype and sequencing of the lasR gene. A significant increase in the frequency of isolates with the sheen positive phenotype was observed in isolates between 1993 and 2021. Extracellular protease activity was lower among the sheen positive isolates and a defined lasR mutant. Cloned lasR alleles from the sheen positive isolates were loss of function or dominant negative and differed in sequence from previously reported ocular lasR mutant alleles. Insertion elements were present in a subset of independent isolates and may represent an endemic source from some of the isolates. Retrospective analysis of patient information suggested significantly better visual outcomes for patients infected by sheen positive isolates. Together, these results indicate an increasing trend towards lasR mutations among keratitis isolates at a tertiary eye care hospital in the United States. Deleted: . quorum sensing will mediate population density 99 dependent collective responses … 100